Desalination industry in the United Arab Emirates (UAE) : lessons for Singapore from the UAE's experience. - Behnke, Daniel. (2008)
The desalination industry has emerged as one of the key growth industries as the world faces decreasing freshwater supply. Young economies such as the United Arab Emirates (UAE), in particular Dubai, and Singapore are both developing their desalination clusters as part of their strategy to be not only self-sufficient in water but to also become the regional desalination hubs, providing desalination resources to the water-stressed countries in the world.